User Satisfaction Analysis of PDAM’s CATER System using Heuristic-SUS Evaluation - Seno Purdayanto, Stefanus Adin; Tanaem, Penidas Fiodinggo (Sistemasi: Jurnal Sistem Informasi, 2025)
The Regional Drinking Water Company (PDAM) of Salatiga City, as a provider of clean water services, has implemented a web-based Meter Recording System (CATER) to enhance operational efficiency. However, the system's effectiveness has not been comprehensively evaluated in terms of usability, despite this factor being crucial for employee productivity and service quality. This study aims to assess the usability level of the CATER system by combining the Heuristic Evaluation (HE) and System Usability Scale (SUS) methods to identify the system's strengths and weaknesses and provide evidence-based recommendations for improvement. The evaluation results show that the system generally demonstrates good usability, with the highest HE scores in Visibility of System Status (89%) and Aesthetic Design (88%), indicating an informative and consistent interface. However, weaknesses were identified in the areas of Recognition Rather Than Recall (68%) and Help Documentation (75%), suggesting a need for workflow simplification and more intuitive user guidance. The average SUS score of 75 (classified as Acceptable) supports the finding that the system is generally well-received by users, though there is still room for improvement. Based on these findings, the study recommends improvements focusing on workflow simplification, the development of more contextual help features, and optimization of error prevention mechanisms. This study’s results are not only valuable for the further development of the CATER system but also serve as a reference for evaluating similar systems in other public utility sectors.